Natural speed observer for nonsalient AC motors - Chen, Jiahao (2021)
This letter addresses experimental validation of the reduced-order natural speed observer design for position sensorless drive with nonsalient permanent magnet synchronous motor. The natural speed observer and the active flux estimator are connected in a cascaded fashion, which results in a simple sensorless algorithm that needs only to tune one bandwidth parameter for flux estimation and one bandwidth parameter for speed observation. Experimental results of high speed reversal test, zero speed stopping test, and slow speed reversal test are included, where the practice of applying nonzero d-axis current at zero speed has shown to be effective for loaded zero speed stopping test, but it causes zero-speed lockedup at slow speed reversal with acceleration rate of 50 r/min/s. Four remedies are compared to improve the slow speed reversal test and the proposed method gives almost ramp actual speed waveform, nondiverging q-axis current and smooth transition in position waveform during slow zero speed crossing. A new dynamic expression of the active flux is proposed and with the aid of the active flux concept, the proposed sensorless algorithm is also applicable to various types of ac motors.